Fully printable perovskite solar cells with highly-conductive, low-temperature, perovskite-compatible carbon electrode. (April 2018) - Jiang, Pei; Jones, Timothy W.; Duffy, Noel W.; Anderson, Kenrick F.; Bennett, Robert; Grigore, Mihaela; Marvig, Paul; Xiong, Yuli; Liu, Tongfa; Sheng, Yusong; Hong, Li; Hou, Xiaomeng; et al.
Abstract: We obtain a novel kind of highly-conductive, low-temperature and perovskite-compatible carbon paste treated with the functional additives of titanium (IV) isopropoxide and acetic acid. The functional additives in the carbon paste can in si-tu generate newly complex polymeric Ti-O-Ti species acting as binder and plasticizer. It helps the electrical conductivity of carbon film increase to 1.13 × 10 4  S m −1, which corresponds to a sheet resistance of 4 Ω □ − 1 for a typical 20 μm film, superior to the transparent FTO/ITO electrode (15 Ω □ − 1 ). Then the carbon film is applied as the low-temperature carbon electrode into fully printable mesoscopic perovskite solar cells and a champion efficiency of 14.04% is achieved. Meanwhile, the series resistance of device based on low-temperature carbon electrode can be reduced from 21 to 13 Ω cm 2, compared to device based on high temperature carbon electrode only. This low-temperature, low cost, highly-conductive carbon film shows promising application in the future module design of fully printable mesoscopic perovskite solar cells. Graphical abstract: Functional additives of titanium (IV) isopropoxide, acetic acid, and α-terpineol which can generate polymeric Ti-O-Ti species acting as binder was developed and deployed to prepare low temperature carbon paste. With the presence of the functional additives, the low-temperature carbon paste exhibits high electrical conductivity of 1.13 × 10 4  S m −1, which corresponds to a sheet resistance of 4.4 Ω □ −1 for a typical 20 μm film, superior to the transparent FTO/ITO electrode (15 Ω □ −1 ) and is robust and compatible with perovskite. Meanwhile, it can further decrease the series resistance of fully printable mesoscopic perovskite solar cells (MPSCs) from 21 Ω cm 2 to 13 Ω cm 2  by initially adjust the structure of MPSCs and also brings a new perspective for its large scale application. Image 1